S-1 for treatment of advanced hepatocellular carcinoma: a systematic review of the literature - Huang, Wu-Kui; You, Li-na; Yang, Shu-Fa; Liu, Deng-Yao; Liu, Mo; Fan, Xi-Wen (Contemporary Oncology/Współczesna Onkologia, 2017)
Hepatocellular carcinoma (HCC) is the most common liver neoplasm worldwide. Based on its potent inhibition of dihydropyrimidine dehydrogenase (DPD), S-1 is expected to be more active than other fluoropyrimidines against HCC with DPD activity. This systematic review was aimed to assess the efficacy and safety of S-1 for treatment of advanced HCC. PubMed, the Cochrane Library, EMBA- SE, and ClinicalTrials.gov were searched using the terms “Hepatocellular Carcinoma” or “HCC” or “Hepatoma” or “Liver cancer” and ‘‘S-1’’. Outcomes of main interest included overall survival (OS) and toxicities. We identified four studies of S-1 treatment alone from 1059 references, including a total of 272 patients. There were two original articles and two conference abstracts. The percentage of male patients ranged from 88 to 91.3% and median age ranged from 59 to 70 years. Median OS ranged from 8.6 to 16.5 months. The incidences of toxicity of more than 50% were thrombocytopaenia and fatigue. According to the original description, toxicities were acceptable. The current evidence from the available clinical studies suggests that S-1 may be an effective and tolerable treatment for advanced HCC. Further clinical studies are warranted to further investigate this treatment option.